CRAMPS - Erdal Gilgil; Bülent Bütün (Archives of Rheumatology, 2002)
Cramp is the painful, involuntarily contraction of the skeletal muscle. Idiopathic nocturnal muscle cramp is the most frequent form, though there are many other clinical conditions, leading to painful muscle contractions, that should be taken into consideration for a favourable diagnosis and management. Most of the idiopathic cramps last for a few minutes. Episodes with a duration of longer than ten minutes necessitate further investigations. For a proper differential diagnosis, it should be elucidated whether the muscle spasm is associated with rest or exertion, the muscle responds to percussion and what like the relaxation of the muscle is.